The effect of Bank Clerks' human service quality on customer satisfaction: The mediating role of rapport - Ji-Hwan Moon; Bo-kyeong Kim; Jae-Ho Yang (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to investigate the impact of bank clerks' human service quality(HSQ) on customer sat-isfaction (CS), as well as the effect of rapport established between the service provider and the customer on satisfaction. Design/methodology/approach: This study conducted quantitative approach with a survey over five days (from April 7 to 11, 2023) by Macromill Embrain, a professional survey agency, among consumers who had recently visited a bank and had experience using face-to-face services. Findings: The three sub-factors of HSQ, namely professionalism, reliability, and interactivity, had a significant positive impact on the formation of rapport with customers. The sub-factors of rapport, namely enjoyable interaction (EI) and personal connection (PC), were also affected by HSQ. The rapport formed in this way had a significant positive effect on CS. Therefore, the quality of human service provided by bank clerks plays a crucial role in building rapport and ultimately leads to CS. Research limitations/implications: In the financial industry, building rapport between service providers and cus-tomers has a positive effect on trust. With the rise of internet-only banks, it is crucial to establish a rapport with customers to provide differentiated services that cannot be offered by internet-only banks due to their limited avail-ability and business hours. This will also help prevent customers from switching to internet-only banks. Originality/value: This study recognizes that although there are many online-only banks, there is still a customer base that favors traditional banks. The paper aims to explore, from both theoretical and practical perspectives, whether meeting the needs of these customers and providing human service quality and rapport in competition with online banks can address the fundamental issue of customer satisfaction. Therefore, this study seeks to empha-size the importance of HSQ in driving CS, explore the most efficient and effective ways for banks to manage this quality for the continuous acquisition of loyal new and existing customers.
Keywords: 650; Bank Clerks' human service quality; Rapport; Enjoyable interaction; Personal connection; Customer satisfaction